THE EFFECT OF DRAGON FRUIT ON INCREASING HEMOGLOBIN LEVELS IN ADOLESCENT WOMEN: LITERATURE REVIEW - Azhar, Ilmannafi'a; Wijayanti, Wijayanti; Wulandari, Retno (Journal of Advanced Nursing and Health Sciences, 2024)
Background : Adolescent girls have a high risk of experiencing anemia, this is caused by loss of iron during menstruation. Adolescent girls have a higher risk of developing anemia than adolescent boys because adolescent girls experience menstruation every month and there is a desire to eat less so that the body lacks important nutrients such as iron. Pharmacological therapy for anemia by administering Fe supplements. However, administering drugs and supplements causes side effects so that people look for alternative treatments other than pharmacological therapy. One alternative to overcome anemia is by consuming dragon fruit. Objective : To analyze in a literature review the effect of dragon fruit on increasing hemoglobin levels in adolescent girls. Method : This research uses a systematic literature review method. Journal search via PUBMED, Google Scholar, Semantic Scholar and Science Direct databases. The journal used was 10 articles. Results : Based on a review of 10 articles, it can be concluded that dragon fruit has been proven to have an effect on increasing hemoglobin levels in young women.